?PROXIMATE COMPOSITION, SOME NUTRITIONALLY VALUABLE MINERALS AND FUNCTIONAL PROPERTIES OF WALNUT (TETRACARPIDIUM CONOPHORUM (MUELL. ARGo) FLOUR - Edema, Mary 0; Okieimen, F E (Biological Sciences - PJSIR, 2000)
FuJI fat walnut (Tetracarpidium conophorum) seed flour was produced and evaluated for proximate and nutritionally valuable mineral composition and functional properties. The proximate composition of walnut was characterized by relatively high protein (14.75%), total carbohydrates (18.87%), fat (51.68%), crude fibre (1.16%) and ash (3.73%). The mineral analysis showed that seed flour was rich in the content of sodium, potassium and phosphorus. The foaming capacity and the least gelation concentration of the seed flour were found to be 7.8% and 5.lO%, respectively. The effects of dilute solutions of NaCI and KCI on some functional properties of the seed flour were also examined. The results indicated that addition of NaCI or KCI solution improved the functional properties of the seed flour.